Compendium of histology : a theoretical and practical guide - Rehfeld, Anders; Nylander, Malin; Karnov, Kirstine (Springer, 2017)
This book has been designed to help medical students succeed with their histology classes, while using less time on studying the curriculum. The book can both be used on its own or as a supplement to the classical full-curriculum textbooks normally used by the students for their histology classes. Covering the same curriculum as the classical textbooks, from basic tissue histology to the histology of specific organs, this book is formatted and organized in a much simpler and intuitive way. Almost all text is formatted in bullets or put into structured tables. This makes it quick and easy to digest, helping the student get a good overview of the curriculum. It is easy to locate specific information in the text, such as the size of cellular structures etc. Additionally, each chapter includes simplified illustrations of various histological features. The aim of the book is to be used to quickly brush up on the curriculum, e.g. before a class or an exam. Additionally, the book includes guides to distinguish between the different histological tissues and organs that can be presented to students microscopically, e.g. during a histology spot test. This guide lists the specific characteristics of the different histological specimens and also describes how to distinguish a specimen from other similar specimens. For each histological specimen, a simplified drawing and a photomicrograph of the specimen, is presented to help the student recognize the important characteristics in the microscope. Lastly, the book contains multiple "memo boxes" in which parts of the curriculum are presented as easy-to-remember mnemonics